The conditions of local self-diagnosability of failure diagnosis models at the system level - Крамаренко, М. Б.; Буров, Е. В. (Eastern-European Journal of Enterprise Technologies, 2012)
Defined conditions of local self-diagnosis for a full lattice of the system-level fault diagnosis models in case of t-diagnosable requirement. In paper are proposed conditions for self-diagnostics of a single computer system module based only on testing results obtained by this module and modules directly connected with it